NEPHTYIDAE (ANNELIDA; POLYCHAETA) DO LITORAL DO ESTADO DO PARANÁ (BRASIL) - Lana, Paulo da Cunha (Revista Nerítica, 1986)
Nephtyidae (Annelida; Polychaeta) from the Paraná coast (Brazil) The Nephtyidae from the Paraná coast (SE Brazil) are represented by 7 species in 3 genera, namely Nephtys acrochaeta, N. squamosa, N. fluviatilis, N. simoni, Inermonephtys palpata, Aglaophamus juvenalis and Aglaophamus uruguayi. Inermonephtys palpata, previously known from Australia, is recorded for the first time in Atlantic waters. Nephtys simoni is also a new record to the Brazilian coast. A key and descriptions, besides some comments on geographical distribution, are provided for all species examined.